From the shadows - Benn, James R. (Benn, James R. Billy Boyle World War II mystery., 2022)
"Following their mission in the Soviet Union, Billy, Kaz, and Big Mike are sent to southern France for what should be a simple assignment: to serve as security for Royal Navy Commander Gordon Stewart, head of the Special Operations Executive's Section F in Algiers. Stewart's mission is to work with Resistance leaders in liberated areas to gather information that will help track down Vichy officials and other traitors who escaped with the retreating Germans. Stewart has received multiple death threats, and there has already been one attempt on his life in Algiers. Over the course of his investigation, Billy learns that Stewart has many enemies in both the SOE and the Resistance, linked to a fatal Resistance uprising. Diana Seaton, Billy's wartime lover, crosses paths with him as she and legendary SOE agent Christine Granville embark on a humanitarian mission on behalf of those killed while helping the SOE. The race to find an important witness leads Billy to the legendary 442nd Regimental Combat Team, a unit made up of Nisei soldiers that went on to become the most highly decorated unit in the history of the US Army"--